Let Us Celebrate 20 Years of Struggle! - Jalandoni, Luis (Kasarinlan: Philippine Journal of Third World Studies, 2007)
A speech delivered at the 20th National Democratic Front (NDF) anniversary celebration in Brussels, Belgium, April 23, 1993.